APAKAH PERCEIVED ENJOYMENT MEDIATOR DALAM MENGUJI EFEK PERCEIVED EASE OF USE TERHADAP BEHAVIORAL INTENTION? - Sjahruddin, Herman; Halim, Ardiansyah; Ramli, Virginia Shera Oktavia; Suan, Gustaf Arminto; Manek, Landriana Un; Irvine, Teddy (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The rapid development of technology has a positive impact on the Indonesian economy as seen by the tendency of people to switch from using cash as a means of payment to using non-cash payments, which are more economical and efficient for transactions. This research is a perceptual research that places perceived enjoyment as a mediator in explaining the effect of perceived ease of use on the behavioural intention of DANA e-wallet users. This perceptual study involved 55 students as respondents, the data was analysed using structural equation modelling with the help of Smart PLS-4. The findings of this study provide evidence that high perceived ease of use has a real impact in increasing perceived enjoyment and behavioural intention. The other causality, namely low perceived enjoyment, cannot make a meaningful contribution to behavioural intention. The role of perceived enjoyment as a mediator is not proven in explaining the effect of perceived ease of use on behavioural intention.